Crystals : growth, morphology, and perfection - Sunagawa, Ichirō (Cambridge University Press, 2005)
Understanding how and why crystals nucleate and grow is important not only for modern technologies, but also in understanding the interior of the Earth and biomineralization. This clear explanation of the atomic processes behind crystal growth, and case studies of complex systems is essential reading for advanced graduates and researchers.